Orlando Magic Co-Founder Pat Williams (Thirty Minute Mentors). - Mendler | Thirty Minute Mentors, Adam (linkedin.com, 2022)
Learn how lessons from on the court translate to leadership lessons from Pat Williams, co-founder of the NBA's Orlando Magic and former general manager of the Philadelphia 76ers.